PENDIDIKAN KARAKTER DI PERGURUAN TINGGI - Lisnawati (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2022)
Abstract This research aims to analyse the implementation of student character development in higher education. Through a literature study, this research identifies various efforts made by universities to shape good student character, such as through curriculum, extracurricular activities, and campus environment. The results show that student character development in higher education is very important to produce graduates who not only have academic competence, but also have strong moral and ethical values. However, there are still some challenges in the implementation of character development, such as the lack of integration between theory and practice, and the lack of systematic evaluation. Keywords: character development, education, students, moral, ethics